Capsicum annuum L. Response to Highly Diluted Bioactive Compounds Application in Germination and Initial Growth Under Saline Conditions - Ojeda-Silvera, Carlos Michel; Mazón-Suástegui, José Manuel; Murillo-Amador, Bernardo; Batista-Sánchez, Daulemys; Batista-Sánchez, Dailenys; García-Bernal, Milagro (REVISTA TERRA LATINOAMERICANA, 2025)
In line with the green economy concept, food using natural products is gaining importance worldwide. Thus, the present study aims to evaluate the ef fect of Natrum muriaticum (NaM) and Silicea Terra (SiT) as salt stress (NaCl) mitigators on Capsicum annuum L. germination and initial seedling growth of two chili varieties. The experiment was performed under controlled conditions, using a completely randomized design with a factorial arrangement of (2A × 3B × 5C), where factor A is the two varieties (Santa Fe and Jalapeño M); factor B is the three levels of NaCl (0, 50 and 100 mM) and factor C is the centesimal dynamizations (CH) of the highly diluted bioactive compounds (HDBC) Natrum muriaticum (NaM): NaM-7CH, NaM-13CH and Silicea terra (SiT): SiT-7CH, SiT-13CH. Distilled water (DW) was used as a control treatment for a total of 30 treatments with four replicates each. The response variables were the germination percentage (GP), germination rate (GR), and, af ter 14 days, the height of the seedlings (HS), radicle length (RL), fresh and dry radicle biomass, and aerial part. Analysis of variance and multiple comparisons of means were performed (Tukey HSD P ≤ 0.05). The results show that NaM-7CH and SiT-7CH applications significantly increased GP, RL, and radicle and aerial fresh and dry biomass parts. The highest response was recorded in RL with NaM-7CH treatment, 57.8% in Jalapeño M variety, and 86.3% in Santa Fe variety with respect to the control treatment seedlings without HDBC (DW). In general, a NaM anti-stress ef fect was observed, demonstrating its ef fectiveness and great potential in sustainable organic agriculture as a low-cost alternative to mitigate the negative ef fects of abiotic stress.